Routine drug resistance testing in proviral HIV‐1 DNA: Prevalence of stop codons and hypermutation, and associated factors. Issue 9 (13th April 2019) - Alidjinou, Enagnon Kazali; Deldalle, Joséphine; Robineau, Olivier; Hallaert, Christophe; Meybeck, Agnès; Huleux, Thomas; Ajana, Faiza; Hober, Didier; Bocket, Laurence
Abstract: We investigated the presence of stop codons (SC) and/or hypermutation (HM) in HIV‐1 DNA sequences generated for routine drug resistance testing in proviral HIV‐1 DNA, and sought for associated factors. At least one SC was identified in 6.2% of HIV‐1 DNA sequences, among which 54.8% were hypermutated. The defective virus group (SC w/o HM) was similar to the non‐SC group regarding the characteristics of HIV‐1 infection, and before drug exposure. In addition, the HIV‐1 DNA levels were not different between both groups. Sequences with SC/HM displayed a higher proportion of RAMs. The impact of the SC/HM associated RAMs on clinical responses requires further investigation. Highlight: HIV‐1 drug resistance genotyping can be performed using proviral DNA. Stop codons and hypermutation (SC/HM) are sometimes detected in HIV‐1 DNA sequences. SC/HM are associated with a high proportion of resistance associated mutations.